2019
DOI: 10.1177/0023677219832919
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study about the immunomodulatory effects of tramadol and metamizole in a murine model of postoperative ileus

Abstract: Postoperative ileus (POI) is a common complication after abdominal surgery characterized by motility disturbances leading to increased morbidity and mortality in surgical patients. Intestinal manipulation of the murine small bowel is an established animal model resulting in an increased postsurgical inflammation within the intestinal muscular externa and a delayed gastrointestinal transit. Some analgesics have been shown to affect inflammation. In this study, we compared the immunomodulatory effects of two dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…Consistent with earlier findings, we observed a significant increase in the levels of proinflammatory cytokines in the blood of POI animals [ 10 , 29 ]. These inflammatory mediators contribute to the decreased GI motility associated with POI through various mechanisms such as direct cytotoxic effects and induction of nitric oxide (NO) and proteinoid production [ 30 ].…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with earlier findings, we observed a significant increase in the levels of proinflammatory cytokines in the blood of POI animals [ 10 , 29 ]. These inflammatory mediators contribute to the decreased GI motility associated with POI through various mechanisms such as direct cytotoxic effects and induction of nitric oxide (NO) and proteinoid production [ 30 ].…”
Section: Discussionsupporting
confidence: 93%
“…A recent study showed that pain medication reduced the expression of the chemokine CXCL2 in a model of postoperative ileus. 33 Thus, we investigated whether paracetamol, tramadol or metamizole (only in chronic DSS colitis) affects cytokine and chemokine expression in DSS-induced colitis. In acute colitis, mRNA levels of Il6 , Tnfa , Il1b , Il10 , Cxcl1 and Cxcl2 were not significantly elevated upon DSS treatment and there was no difference between mice receiving DSS alone and those receiving DSS + paracetamol or DSS+tramadol (Figure 4a–f).…”
Section: Resultsmentioning
confidence: 99%